1983
DOI: 10.1111/j.1432-1033.1983.tb07418.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Melanoma Cell Plasminogen Activator

Abstract: The plasminogen activator from a human melanoma cell line was purified with immunoadsorption as a major step. The cells were cultured in the presence of aprotinin in order to avoid proteolysis. A three-step purification involved adsorption on antibodies to porcine tissue plasminogen activator before chromatographies on arginineSepharose and Sephadex G-150. All solvents contained Tween-80 (0.01 %) and, except for the last step, aprotinin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0
2

Year Published

1983
1983
1990
1990

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(31 citation statements)
references
References 21 publications
3
26
0
2
Order By: Relevance
“…Preparations apparently exhibiting only S-chains have also been reported [4]. Plasmin (apart from giving the two-chain cleavage) cleaves off the extra N-terminal tripeptide in the L-chain [2], thus removing the N-terminal S/L heterogeneity in the A-chain. Therefore, the A-chain is always S-type.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Preparations apparently exhibiting only S-chains have also been reported [4]. Plasmin (apart from giving the two-chain cleavage) cleaves off the extra N-terminal tripeptide in the L-chain [2], thus removing the N-terminal S/L heterogeneity in the A-chain. Therefore, the A-chain is always S-type.…”
Section: Introductionmentioning
confidence: 99%
“…First, direct sequence analysis revealed that the molecules consist of polypeptides starting at different positions [2]. Thus, the material A second variation is reflected by molar mass differences, possibly due to internal carbohydrate differences in the A-part, constituting type I and type II activator molecules [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations